The structure, vacancy characteristics, and magnetic properties of GdMn1-xCrxO3 ceramics. Issue 11 (1st June 2021) - Dai, H.Y.; Wang, M.M.; Li, T.; Liu, D.W.; Yang, Y.; Chen, Z.P.
Abstract: To investigate the evolution of the structural and enhanced magnetic properties of GdMnO3 systems induced by the substitution of Mn with Cr, polycrystalline GdMn1- x Cr x O3 samples were synthesized via solid-state reactions. XRD characterization shows that all GdMn1- x Cr x O3 compounds with single-phase structures crystallize well and that Cr 3+ ions entering the lattice sites of GdMnO3 induce structural distortion. SEM results indicate that the grain size of the synthesized samples (a few microns) decreases as the Cr substitution concentration increases. Positron annihilation lifetime spectroscopy reveals that vacancy-type defects occur in GdMn1- x Cr x O3 ceramics and that the vacancy size and concentration clearly change with the Cr content. The temperature and field dependence of the magnetization curves show that Cr substitution significantly influences the magnetic ordering of the gadolinium sublattice, improving the weak ferromagnetic transition temperature and magnetization of GdMn1- x Cr x O3 . The enhanced magnetization of GdMn1- x Cr x O3 is closely related to the vacancy defect concentration.